Applying a cumulative risk framework to drinking water assessment: a commentary - Tasha Stoiber; Alexis Temkin; David Andrews; Chris Campbell; Olga V. Naidenko (BMC, 2019)
Abstract The health risks of drinking water contaminants and the economic benefits of drinking water standards are typically assessed one chemical at a time, an approach that misses the health impacts of co-occurring contaminants in drinking water. In contrast, a cumulative risk framework has become common in air quality evaluations such as the U.S. Environmental Protection Agency's National Air Toxics Assessment. We posit that the drinking water field would benefit from making the transition to a unified assessment framework for multiple contaminants that can overcome the long-standing challenge of treating cancer and non-cancer contaminants separately. Here we present a cumulative risk methodology that combines a risk-based cancer metric with a weighted health indicator index for non-cancer contaminants and incorporates disability weights from the Global Burden of Disease study. Our methodology generates a numeric toxicity score reflecting the potential health impacts for the sum of contaminants present in each sample of drinking water. Further research is needed to refine the risk and toxicity parameters for specific contaminants and to address the mode of interaction between co-occurring chemicals. As this cumulative risk model goes through future refinements, we anticipate that it would provide information that can help communities and policy makers evaluate different options for drinking water treatment.